Problematization of Teaching Practices and Teaching Contextualization - Rodríguez-Sosa, Jorge (2018)
This article is a reflection in three planes: the first one, how teachers problematize their own practices given the complexity of the scenarios that they must face daily in classrooms; the second one, how teaching problematization is perceived in the academic and school world and the third one, hoy many and how contents, methodological tools and training forms, which are necessary to strengthen teachers’ abilities and attitudes prone to problematization, have been assumed by continuous teaching training programs. It is concluded with a joint reflection that tries to establish the link between these planes.